A Quantitative Approach to Measure Tax Competitiveness Between EU Countries - Konstantinos J. Liapis; Christos L. Galanos; Evangelos D. Politis; Dimitrios D. Kantianis (International Journal of Economic Sciences and Applied Research, 2014)
The basic purpose of the study is to find a metric-variable of competitiveness for each country's tax regime and to assess the impact of tax regime differentiation across the common market. A country adopting competitive taxation policies manages to attract productive factors, funds and investments from other intra- and inter-countries. The value added tax (VAT), property tax as well as corporate and personal taxes are examined for the twenty seven (27) European Union (EU) countries. The methods applied consist of Least Square Dummy variable models and the results from the estimations for each one of the aforementioned taxes are integrated into a new total competitiveness taxation index (TCTI), following weighted hierarchical quantitative approaches. Our findings suggest that significant differences still exist between the countries examined and the application of diverse tax regime systems results in various tax performances. Using the above procedure, we also find that subgroups exist within the (27) EU countries and that EU lacks taxation policies with common rules or restrictions. Following the TCTI methodology proposed by this research, a tool for monitoring EU tax regimes is introduced in order to assist in the EU integration to a common tax regime.
Keywords: H20; C00; R00; 330; Taxation; Public Economics; Tax Regime Structure; Quantitative Methods